2007
DOI: 10.1128/aem.00225-07
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Cellulolytic Gliding Bacterium Cytophaga hutchinsonii

Abstract: The complete DNA sequence of the aerobic cellulolytic soil bacterium Cytophaga hutchinsonii, which belongs to the phylum Bacteroidetes, is presented. The genome consists of a single, circular, 4.43-Mb chromosome containing 3,790 open reading frames, 1,986 of which have been assigned a tentative function. Two of the most striking characteristics of C. hutchinsonii are its rapid gliding motility over surfaces and its contact-dependent digestion of crystalline cellulose. The mechanism of C. hutchinsonii motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
176
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 74 publications
6
176
0
Order By: Relevance
“…Among aerobes, only the cellulolytic gliding bacterium Cytophaga hutchinsonii lacks exocellobiohydrolases and endoglucanases fused to cellulose-binding domains (22). The precise mechanism used by C. hutchinsonii is somewhat mysterious, but it has been suggested that cellulose chains are peeled away from the polymer and transported into the periplasm (23).…”
Section: Discussionmentioning
confidence: 99%
“…Among aerobes, only the cellulolytic gliding bacterium Cytophaga hutchinsonii lacks exocellobiohydrolases and endoglucanases fused to cellulose-binding domains (22). The precise mechanism used by C. hutchinsonii is somewhat mysterious, but it has been suggested that cellulose chains are peeled away from the polymer and transported into the periplasm (23).…”
Section: Discussionmentioning
confidence: 99%
“…A putative protein that has 37% sequence identity to Cel9D was identified from the genome of a phylogenetically related bacterium, Cytophaga hutchinsonii (35). Cellulase systems of F. succinogenes and C. hutchinsonii are quite similar and distinct from other cellulolytic bacteria in that both bacteria lack genes encoding proteins with similarity to members from GH6 or GH48; most cellulases in both bacteria are cell associated but lack a carbohydrate binding module, and no cellulosome structures were identified (21,35).…”
Section: Discussionmentioning
confidence: 99%
“…PorT is required for P. gingivalis gingipain secretion, and may interact with other proteins to form the translocation machinery. porT homologs are found in some other members of the phylum Bacteroidetes, such as C. hutchinsonii ATCC 33406, but not in others, such as B. thetaiotaomicron VPI-5482 (13)(14)(15). To identify possible additional components of the gingipain secretion system, we identified 55 genes in addition to porT that were present in P. gingivalis and C. hutchinsonii but absent in B. thetaiotaomicron ( Fig.…”
Section: Identification Of Genes Involved In Gingipain Secretion Bymentioning
confidence: 99%